(untitled) (Journal of the College of Basic Education, 2023)
The educational process has developed widely in our modern era through the use of various motor learning methods that can have a clear impact and a prominent role in bringing the learner to the level of better skill performance, as it has become an important basis on which to rely on in planning learning processes and has expanded to include the perceptual and cognitive levels. Which requires the learner’s positivity in education in order to show students’ latent abilities and improve them, and the methods used in teaching are no longer suitable for contemporary life, so many methods help to acquire many mental, social and motor skills, and the importance of research lies in using the teaching method that is compatible with the skills that depend on the participation of The student in the learning process in a positive way by conducting a scientific study through which she learns about the impact of the SWOM strategy in using compound exercises and learning some artistic gymnastics skills. The researcher used the experimental approach (designing the two equal groups, which are the control and experimental groups) for its suitability to the problem. The research community was determined by students of the third stage in the Department of Physical Education and Sports Sciences, College of Basic Education - Al-Mustansiriya University for the academic year (2022-2023), and the research sample was chosen by a simple random method (lottery) from the original research community, with (30) students (15) students for each A group of the most important research procedures is the initiation of defining the skills and evaluation forms for the ground movements under study, and then the researcher conducted an equivalence between the two groups, and then educational units were prepared according to the SOM strategy using compound exercises, one educational unit per week and a time of 90 minutes, and the researcher used the statistical bag to extract the most important results that she reached. The researcher reached the conclusions, the most important of which is that the use of the Sowm strategy led to an improvement in the performance of some basic artistic gymnastics skills of the experimental group. The adoption of the SOM strategy contributed to the development of thinking among the members of the experimental group. As for the most important recommendations, they are: Using the Sowm strategy in learning the rest of the artistic gymnastics skills and in other age stages, because it helps in developing the student’s thinking. And the emphasis is on using the SOM strategy in teaching the rest of the subjects in physical education for the purpose of learning skills and retaining information for them